Super-regenerative receiver at 433MHz - Carmo, João Paulo Pereira (2011)
This paper presents a receiver for operation in the 433 MHz ISM band. The selected architecture explores the super regeneration phenomena to achieve a high sensitivity for applying in wireless implantable microsystems. This radio frequency (RF) chip can be supplied with a voltage of only 3 V for demodulating signals with powers in the range [ 100, 40] dB. The codulation (modulation and coding) scheme of the binary data is a variation of the Manchester code combined with OOK (on/off keying) modulation. The AMIS 0.7 µm CMOS process was selected for targeting the requirement to fabricate a low cost receiver, whose prototype was integrated in a die with an area of 55 mm2. Also, this receiver is fully compatibility with commercially transmitters for the same frequency.